Art, Expression, and Censorship: Navigating Freedom of Artistic Expression in Indonesia (Indonesian Art and Justice Review, 2024)
The relationship between art and censorship in Indonesia is a complex and often contentious issue, especially in the context of political, religious, and moral sensitivities. This paper explores the ongoing tension between artistic freedom and the state’s regulatory frameworks in Indonesia, where artists frequently navigate the challenges of censorship imposed by both government and societal pressures. It examines notable instances of artistic works facing censorship, from visual art and performance to literature and film, and discusses the ethical implications of these restrictions on freedom of expression. By analyzing the intersection of law, politics, and culture, the paper considers how artists in Indonesia continue to push boundaries and challenge the status quo, and the role of art in preserving democratic spaces for free expression.